Diagnostic and prognostic value of the Creatinine/Cystatin C ratio for low muscle mass evaluation among US adults - Shi, Shanshan; Jiang, Yizhou; Chen, Weihua; Chen, Kaihong; Liao, Ying; Huang, Kun (Frontiers in Nutrition, 2022)
Background: Identifying patients with low muscle mass is crucial for the diagnosis of sarcopenia. Although the Creatinine/Cystatin C (Cr/CysC) is recommended as a simplified indicator to identify patients with low muscle mass, its ability to assess muscle mass and predict a poor prognosis has not been validated. We aimed to determine the diagnosis value of Cr/CysC for low muscle mass and examine the association of Cr/CysC with mortality. Methods: In this cohort study we analyzed data from the National Health and Nutrition Examination Survey from 1999 to 2002. Follow-up was conducted up to December, 2015. Appendicular skeletal mass was calculated based on DXA scans. Low muscle mass was defined referring to five international diagnostic criteria. The diagnostic value of Cr/CysC as a replacement indicator of muscle mass was measured using area under the curve, positive percent agreement, negative percent agreement and kappa. Cox proportional hazards regression models were developed to examine the association between Cr/CysC and risk of mortality. Results: This cohort study of 3741 adults comprised 1823 females (48.73%), with a weighted mean (SE) age of 44.46 (0.43) years. The positive percent agreement of Cr/CysC for the diagnosis of low muscle mass was poor (40.23% to 58.74%), except for Foundation of the National Institute of Health (FNIH) criteria (80.90% to 58.97%). But the negative percent agreement of Cr/CysC for the diagnosis of low muscle mass was high (males: 62.15% to 88.17%; females: 55.26% to 82.30%). Moreover, the risk of death was reduced by 2% per 0.01 unit increase in Cr/CysC (aHR, 0.98; 95% CI, 0.98-0.99, P < 0.001). Conclusions: Cr/CysC performed well not only in identifying non-sarcopenia cases, especially when based on FNIH diagnostic criteria, but also in revealing a positive association with higher risk of mortality. Expanding the use of Cr/CysC would allow for early and targeted treatment of sarcopenia.